Association Between Rare Earth Element Cerium and the Risk of Oral Cancer: A Case-Control Study in Southeast China - Baochang He; Baochang He; Baochang He; Jing Wang; Jing Lin; Jing Lin; Jinfa Chen; Zhaocheng Zhuang; Zhaocheng Zhuang; Yihong Hong; Yihong Hong; Lingjun Yan; et al. (Frontiers Media S.A., 2021)
Cerium (Ce), the most abundant of rare earth elements in the earth's crust, has received much health concerns due to its wide application in industry, agriculture, and medicine. The current study aims to evaluate whether there is an association between Ce exposures and the risk of developing oral cancer. Serum Ce level of 324 oral cancer patients and 650 matched healthy controls were measured by inductively coupled plasma mass spectrometry. Association between Ce level and the risk of oral cancer was estimated with an unconditional logistic regression model. Serum Ce concentrations in the oral cancer patients and controls were 0.57 (0.21-3.02) μg/L and 2.27 (0.72-4.26) μg/L, respectively. High level of Ce was associated with a decreased risk of oral cancer (OR: 0.60, 95% CI: 0.43-0.84). Stronger inverse associations between high level of Ce and oral cancer risk were observed among those with smoking (OR: 0.46, 95% CI: 0.27-0.79), drinking (OR: 0.50, 95% CI: 0.26-0.96), limited intake of leafy vegetables (OR: 0.40, 95% CI: 0.22-0.71) and fish (OR: 0.52, 95% CI: 0.33-0.83). There were significant multiplicative interactions between Ce level and alcohol drinking or intake of leafy vegetables and fish (all Pinteraction <0.05). This preliminary case-control study suggests an inverse association between high serum Ce level and the risk of oral cancer. Further prospective studies with a larger sample size are needed to confirm the findings.